De l’histoire à la fiction : la réception des Memoirs of the Life of Colonel Hutchinson - Claire Gheeraert-Graffeuille (Sillages Critiques)
« The Life of John Hutchinson », written by Lucy Hutchinson between 1664 and 1667, was published as the Memoirs of the Life of Colonel Hutchinson in 1806 by a descendant of the Hutchinson family. The Memoirs soon became a best-seller and were reprinted throughout the nineteenth century. From the 1830s onwards, abridged versions of the Memoirs, biographies of Lucy Hutchinson, but also novels and plays derived from the Memoirs were published. The purpose of this study is to examine these readings and appropriations of the first edition of the Memoirs. While Lucy Hutchinson consistently rejected the genre of romance to privilege history, it appears that in the nineteenth-century biographies and adaptations of the Memoirs her historical undertaking is obscured by sentimental and domestic readings. This paper on the reception of the Memoirs argues that the reasons for the nineteenth-century dehistoricization and fictionalization of the Memoirs lie in the generic hybridity of the work as well as in the insistent invitation to readers to read the Memoirs as a historical novel.